2008
DOI: 10.1039/b803956a
|View full text |Cite
|
Sign up to set email alerts
|

Surface Pourbaix diagrams and oxygen reduction activity of Pt, Ag and Ni(111) surfaces studied by DFT

Abstract: Based on density functional theory calculations we investigate the electrochemically most stable surface structures as a function of pH and electrostatic potential for Pt(111), Ag(111) and Ni(111), and we construct surface Pourbaix diagrams. We study the oxygen reduction reaction (ORR) on the different surface structures and calculate the free energy of the intermediates. We estimate their catalytic activity for ORR by determining the highest potential at which all ORR reaction steps reduce the free energy. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
525
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 538 publications
(579 citation statements)
references
References 28 publications
(61 reference statements)
36
525
0
1
Order By: Relevance
“…In these approaches, termed ab initio thermodynamics in the context of heterogeneous catalysis23, 99 and computational hydrogen electrode in the context of electrocatalysis,100, 101 the surrounding gas or liquid phase is represented by reservoirs, which then allows to compare structures of differing composition within a grand‐canonical framework. This leads to the prediction of thermodynamically stable (surface) phases either in form of phase diagrams as a function of the chemical potentials of the reactants or in form of Pourbaix diagrams as a function of pH and applied potential.…”
Section: Theory and Molecular Modelling: Understanding Catalysts Undmentioning
confidence: 99%
“…In these approaches, termed ab initio thermodynamics in the context of heterogeneous catalysis23, 99 and computational hydrogen electrode in the context of electrocatalysis,100, 101 the surrounding gas or liquid phase is represented by reservoirs, which then allows to compare structures of differing composition within a grand‐canonical framework. This leads to the prediction of thermodynamically stable (surface) phases either in form of phase diagrams as a function of the chemical potentials of the reactants or in form of Pourbaix diagrams as a function of pH and applied potential.…”
Section: Theory and Molecular Modelling: Understanding Catalysts Undmentioning
confidence: 99%
“…We note that our thermodynamic analysis is within the scheme of the concerted proton-electron transfer 29 , where transfer of single (or multiple) proton and electron occurs in a concerted elementary step, instead of stepwise mechanisms in which the electron and proton are transferred sequentially. Consequently, all equilibrium potentials of (electrochemical) reaction steps contain the same G(H + )/e 0 term (G(H + ) is the free energy of proton and e 0 is the magnitude of its charge) and the activities/overpotentials of catalysts exhibit no pH dependences 23 . The stability of solvated metal ionic species, which requires decoupling of protons and electrons in reaction free energies (relative to the SHE reference) and incorporation of available experimental data for free energies of solvated metal ionic species vs. solid states 41 , are not included in this work.…”
Section: Bulk Phase Diagram and Oxygen Chemical Potentialmentioning
confidence: 99%
“…Although these recent studies have demonstrated that improved exchangecorrelation functionals yield significantly different results than traditional LDA/GGA approaches, these more advanced models have not yet been applied to develop a realistic model of the stable surfaces and their coverage under catalytic conditions. Such effects have been shown to cause significant changes in the predicted ORR activity of Ni metal 23 . Furthermore, detailed experimental characterizations 24 has also observed a correlation between the surface HO* coverage and the ORR activities of LaBO 3 (001) films (B=Cr, Mn, Fe, Co, and Ni).…”
Section: A Introductionmentioning
confidence: 99%
“…Several studies have noted the presence or importance of intermediate species in reactions occurring in metal-oxygen batteries, 51,67 or in other contexts. 59,62,64,65 Finally, it is instructive to compare the present results for an Mg/O2 cell to studies on the Li/O2 system. [35][36][37]66,73 A recent report by Viswanathan et al 37 Table 2.…”
Section: Mgo2 (100) Stoichiometric Surfacementioning
confidence: 99%
“…Limiting potentials were evaluated for two reaction pathways (described below) involving discharge/charge reactions on MgO (100), following the approach of Norskov et al 30,32,35,36,[59][60][61][62] This treatment models the discharge process as a series of adsorption events onto the surface of an existing particle of the discharge product. For illustrative purposes, Figure 6 presents a generic discharge process.…”
Section: Reaction Energiesmentioning
confidence: 99%